Primate resting postures : an adaptation to mammalian herbivory? - Chua, Physilia Ying Shi. (2011)
The functional separation of different particle sizes in the gut of an herbivorous primate is important, as faster excretion of large particles reduces the intake-limitation posed by the long microbial fermentation of plant. This separation functions only along a gravity gradient, therefore, a primate’s resting postures may affect the efficiency of its digestive strategy. Other than in sloths, a primate’s resting postures has not been studied before. To find out if a primate’s resting postures is an adaptation to its diet, the resting postures, amount of rest time, correlation between the rates of ingesta passage time and resting postures, and terrestrial/arboreal adaptations of five groups of primates (Colobinae, Cercopithecinae, Alouattinae, Atelinae and Apes) were studied. Colobinae were observed to rest sitting upright the most. No differences were observed between the groups for the amount of time spent resting. There was also no correlation between the rates of ingesta passage time and resting postures. Colobinae, Alouattinae and Atelinae were observed to be arboreal, Cercopithecinae terrestrial while the Apes were semi-terrestrial. All the groups except for the Apes showed a preference for resting in a sitting upright posture when on the trees as compared to when on the ground.